(untitled) (American Journal of Economics and Business Innovation, 2024)
The basic principle of doing business is that regulations should be relatively easy to comply with and accessible to all who need to use them, so that anyone with talent and good ideas can start and grow a business in the formal sector. In this context, in order to improve access to government services, decentralize government service points, increase awareness of the range of government services and also to attract foreign direct investment in Kenya, the Government of Kenya has adopted a one-stop shop regulatory regime. As regards FDI, the Government considered that by providing investors with a clear and convenient source of information to enable them to compete more effectively on the market, this model could improve transparency and openness. However, studies have shown that foreign direct investment firms continue to withdraw from the Kenya market on grounds of good reasons. For this reason, the study sought to establish the relationship between the one-stop shop regulatory regime and the competitiveness of FID firms in Kenya. The unit of analysis was the management staff of 66 manufacturing FDI firms which were members of Kenya Association of Manufacturers (KAM) in the Nairobi Metropolitan while the unit of observation comprised; human resource manager 1, finance manager 1, marketing manager 1, production manager 1 and CEO/GM/owner 1. Primary data were collected by means of a semi structured questionnaire, while secondary data included the analysis of statistical abstracts from published materials and reports. Data analysis was carried out using the statistical package for social sciences (SPSS) software version 25 as well as descriptive and inferential statistics. The results have shown that the competitiveness of foreign direct investment manufacturing firms in Kenya has been significantly influenced by the one-stop shop regulatory regime. Energy costs were found to have a moderating effect on the influence of innovation strategies on competitiveness of FDI manufacturing firms in Kenya. In particular, the data showed that the competitiveness of foreign direct investment manufacturing firms and their decision to stay or leave the business is influenced by the cost of electricity and petroleum.